Ritual, Spectacle, and Theatre in Late Medieval Seville : Performing Empire - Swift, Christopher (Book collections on Project MUSE., 2023)
From the fall of Islamic Isbīliya in 1248 to the conquest of the New World, Seville was a nexus of economic and religious power where interconfessional living among Christians, Jews, and Muslims was negotiated on public stages. From out of seemingly irreconcilable ideologies of faith, hybrid performance culture emerged in spectacles of miraculous transformation, disciplinary processionals, and representations of religious identity.Ritual, Spectacle, and Theatr.